2023
DOI: 10.3390/metabo13030342
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, Prognostic and Mechanistic Biomarkers of COVID-19 Identified by Mass Spectrometric Metabolomics

Abstract: A number of studies have assessed the impact of SARS-CoV-2 infection and COVID-19 severity on the metabolome of exhaled air, saliva, plasma, and urine to identify diagnostic and prognostic biomarkers. In spite of the richness of the literature, there is no consensus about the utility of metabolomic analyses for the management of COVID-19, calling for a critical assessment of the literature. We identified mass spectrometric metabolomic studies on specimens from SARS-CoV2-infected patients and subjected them to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 139 publications
(264 reference statements)
0
3
0
Order By: Relevance
“…Metabolomic and lipidomic approaches have elucidated numerous circulating lipids that are directly associated with the severity of COVID-19, indicating that lipid metabolism could be a potential target for therapeutic strategies in the treatment and management of the disease (21,22). Circulating lipids play a key function in the pathogenesis of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic and lipidomic approaches have elucidated numerous circulating lipids that are directly associated with the severity of COVID-19, indicating that lipid metabolism could be a potential target for therapeutic strategies in the treatment and management of the disease (21,22). Circulating lipids play a key function in the pathogenesis of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Looking beyond possible literature biases, the wide variety of biomarkers identified is strongly suggestive of confounding variables. One such variable is severity with extensive overlap between biomarkers identified as prognostic and diagnostic [ 9 ]. Danlos et al identified reductions in plasma tryptophan levels and increases in levels of the immunosuppressive metabolite kynurenine in critical care patients as compared to mild cases [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, as reverse transcription polymerase chain reaction (RT-PCR) and rapid antigen testing (RAT) capacity increased dramatically, the focus of metabolomics work shifted to identifying dysregulated pathways and markers for patient vulnerabilities and potential treatment candidates. Whilst many metabolomics studies have been conducted in a variety of matrices including breath [ 5 ], sebum [ 6 ], urine [ 7 ], and saliva [ 8 ], the majority of tests have used peripheral blood as a sampling matrix [ 9 , 10 ]. Whilst more invasive than breath or sebum, for example, peripheral blood has the advantage of being homeostatically regulated and less subject to contamination.…”
Section: Introductionmentioning
confidence: 99%